Marijan Lipovšek - Smrekar, Borut (Glasbenopedagoški zbornik (Ljubljana), 2011)
The article presents cantata Orglar (Organist) by Marijan Lipovšek, written upon one of the most renowned poems by France Prešeren. The composition reveals the author's thorough knowledge of compositional technique and an excellent command of musical dramaturgy. The cantata is written in a definable tonal framework. The characteristic interval is the third, both in the tonal plan and the harmonies, though less explicity in the melodies. Its formal structure is marked off by the ten-strophe poem. The composer has proved outstanding perceptivity in characterising the text through thoughtful utilization of means coming from the oratorial and operatic tradition. Without any doubt, Orglar ranks among the most outstanding Slovenian works of the genre.
Keywords: 20.st.; 20th century; cantata; glasbena analiza; kantate; Lipovšek, Marijan; Lipovšek, Marijan: Orglar; music analysis; Slovenia; Slovenian music; Slovenija; slovenska glasba